2022
DOI: 10.21585/ijcses.v5i4.138
|View full text |Cite
|
Sign up to set email alerts
|

How is computational thinking assessed in European K-12 education? A systematic review

Abstract: Computational thinking (CT) is seen as a key competence of the 21st century and different countries have started to integrate it into their compulsory school curricula. However, there exist only few indications on how to assess CT in compulsory school. This review analyses which tools are used to assess CT in European schools and which dimensions of CT are assessed. We analysed 26 studies carried out between 2016 and 2020 in K-12 in Europe. The results indicate that 18 different tools have been used which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…CT components were considered in the activity design, but a tool measuring CT components was not used to evaluate the effectiveness of the activity. Babazadeh and Negrini (2022) reviewed studies conducted between 2016 and 2020 on CT assessment tools and components evaluated through a systematic literature review. They concluded that there is no assessment tool that fully measures the components of CT, but studies argue that the components of CT generally measure programming skills.…”
Section: Resultsmentioning
confidence: 99%
“…CT components were considered in the activity design, but a tool measuring CT components was not used to evaluate the effectiveness of the activity. Babazadeh and Negrini (2022) reviewed studies conducted between 2016 and 2020 on CT assessment tools and components evaluated through a systematic literature review. They concluded that there is no assessment tool that fully measures the components of CT, but studies argue that the components of CT generally measure programming skills.…”
Section: Resultsmentioning
confidence: 99%